Peningkatan Keterampilan Komunikasi Guru Dalam Proses Pembelajaran Melalui Kegiatan Focus Group Discussion (FGD) Di SD Negeri 06 Situjuah Gadang - Nurma Nurma (JPGI (Jurnal Penelitian Guru Indonesia), 2020)
This research is motivated by the low communication skills of teachers in the learning process at SDN 06 Situjuah Gadang, Lima Puluh Kota. This study aims to improve teacher communication skills in the learning process through FGD activities. This type of research is action research using a qualitative approach. This research data in the form of information about the process and data on the results of actions obtained from observations, the results of teacher skills assessment, discussion and documentation. The data source is the process of implementing Focus Group Discussion (FGD) activities. The results show that there is an increase in research results from Cycle I to Cycle II, this proves that guidance through FGD activity can improve the teacher's communication skills.